Molecular Investigation and Genotyping of Theileria equi and Babesia caballi in Horses in Mus Province, Turkey - OGUZ, B.; ÖZDAL, N.; DEGER, M.S.; BICEK, K. (Journal of the Hellenic Veterinary Medical Society, 2021)
Equine Piroplasmosis (EP) is a tick-borne disease caused by Theileria equi and Babesia caballi of the phylum Apicomplexa. In this study, 102 blood samples were randomly collected from the horses in Mus province of Turkey. PCR analysis, gene sequences, and phylogenetic analyses were carried out for detecting the presence and genotypic characteristics of species that cause piroplasmosis. Four (3.9%) of the 102 horses that were examined were found to be positive for T. equi, while B. caballi was not detected. Theileria equi isolates that were detected in the sequence analyses were found to be 100% identical to the isolates that were isolated from the horses in Turkey, the United States, and South Africa as well. In the phylogenetic analysis, all of the isolates were found to cluster with T. equi sequences in the genotype A. This study, in which we revealed intraspecies sequence heterogeneity of the parasite using the 18S rRNA gene region, provides important epidemiological data for equine piroplasmosis. However, we think that determining the characterization of genotypes that are common in different parts of our country is extremely important in terms of developing new diagnostic tools and vaccines.